INTERNET AS A NEW SPACE FOR HATE CRIMES - Bordolińska, Anna (Człowiek w cyberprzestrzeni, 2020)
The Internet plays an important role in human life and its functioning in society. It is a sphere of implementation of positive actions, but it can also be a space of undesirable phenomena. Internet capabilities make it easier to commit hate crimes and discriminatory actions. The aim of the article is to show how the Internet creates a field for practicing hate speech and how to fight hate crimes with this medium.